Preserving technotronic documents in the archives of Tuva - Hovalyg, Salimaa S. (The New Research of Tuva, 2020)
The article addresses issues of managing storage of technotronic documents (i.e. those of technical origin) in Tuva’s archives. It is a study of technotronic documents preserved in the collections of the National Archives (prior to 07.04.2020 – State Archives) of the Republic of Tuva, as well as at the Aldan Maadyr National Museum, and of institutions of regional government and administration. A large collection of video-, phono- and photodocuments came into being as a result of years of doing documentary and artistic photo and video shoots. Tuvan archives also preserve a number of electronic documents. At the main archive of the republic, photo storage is organized along the same lines as at other archives of video- and photodocuments. However, a number of problems persist, such as the absence of stringent classification (some of the photos are included in personal collections); temperature and moisture control for better preservation of these type of items; wrong regime of storage for photographic negatives; making reserve copies; setting up the copies’ collection; digitalizing photos and phonodocuments; and storing electronic documents. An urgent priority is to set up a Center for Storing Technotronic Documents. Another urgent challenge, the one for the Aldan Maadyr National Museum of the Republic of Tuva, is to organize a catalog and register of the photographic documents in their photo collection. Meanwhile, the bodies of regional government and administration of Tuva, where a slew of audiovisual documents are now produced every year, an important challenge is to organize their storage correctly.